UWB antipodal Vivaldi antenna for monostatic configuration of through wall imaging applications - AHMED, SAJJAD; JORET, ARIFFUDDIN; KATIRAN, NORSHIDAH; PONNIRAN, ASMARASHID; ABDULLAH, M. F. L.; ZAKARIA, ZAHRILADHA; SULONG, MUHAMMAD SUHAIMI (2024)
This article presents an ultra-wideband (UWB) corrugated slit antipodal Vivaldi antenna (CS-AVA) for through wall imaging (TWI) applications. The antenna was designed using Rogers RT-Duroid 5880 material with corrugated slits applied on flares of antipodal Vivaldi antenna (AVA) to improve performance. The proposed antenna operated in frequency band (3.1 GHz to 10.6 GHz) and had reflection coefficient of less than -10 dB. A specific stable gain of around 11.7 dB is achieved with good directivity and fine radiation patterns. Using this monostatic UWB antenna design, a TWI simulation-based experiment was carried out. It has been found that the received signal of the UWB-AVA can be used to detect metallic objects through the wall.